THE CRACKS OF HUMAN NATURE IN PAI CONTRA MAE, BY MACHADO DE ASSIS - Ribeiro Pedroso, Raquel Cristina [UNESP]; Betella, Gabriela Kvacek [UNESP] (Assoc Nac Pos-graduacao Pesquisa Letras & Linguistica, 2020)
Considering the constitution of the modern subject in Machado's books, with objective to analyze the representation of human drivers in the short story Father against Mother, Pai contra mae, published in the collection Rehquias de casa velha, from 1906, by Machado de Assis. The aforementioned tale covers aspects of morality that interweave instincts of cruelty and the nature of evil as a congenital part of social formation. It is intended to describe the reification of man by slavery in the midst of the struggle for self-preservation and soul tendencies for the perception of possible paths in the face of threatening situations.
Keywords: Machado de Assis; Moral; Human drivers; Pai contra mae; Slavery